Survival and treatments in patients with incompletely resected thymoma. (July 2014) - Hamaji, Masatsugu; Omasa, Mitsugu; Chen, Fengshi; Yamada, Tetsu; Sato, Masaaki; Menju, Toshi; Sato, Toshihiko; Aoyama, Akihiro; Sonobe, Makoto; Bando, Toru; Date, Hiroshi
Objectives: the objective of our study was to clarify survival and treatments in patients with incompletely resected thymoma. Methods: between January 1991 and December 2012, 156 consecutive patients who underwent thymectomy with curative intent at Kyoto University Hospital, were evaluated retrospectively. Overall survival and progression-free survival were analyzed using the Kaplan-Meier method, comparing the complete resection group ( n = 141) with the incomplete resection group ( n = 15). Potentially relevant factors for overall survival and progression-free survival in patients with incompletely resected thymomas were analyzed using Cox proportional-hazard models. Results: there was a significant difference in progression-free survival ( p = 0.0012) but not in overall survival ( p = 0.638) following thymectomy in the complete and incomplete resection groups. Adjuvant chemotherapy was performed in 6 (40%) patients and adjuvant radiotherapy in 6 (40%) in the incomplete resection group. In univariate analysis, younger age ( p = 0.073) showed a tendency for better overall survival, and adjuvant chemotherapy ( p = 0.071) showed a tendency for better progression-free survival. Conclusion: our results suggest that patients with incompletely resected thymomas can achieve comparable overall survival to those with completely resected thymomas. Adjuvant chemotherapy for incompletely resected thymomas tends to improve progression-free survival.